Experimental Study on Effect of Reflector Bed Designs Heated by Direct Solar Radiation for Hot Water Storage System - M.Y, YUHAZRI; A.M, KAMARUL; A.H, RAHIMAH; HAERYIP, SIHOMBING; S.H, YAHAYA; K.F, SAMAT; R, IZAMSHAH (2012)
The aim of this research is to investigate the performance of different reflector bed design heated by direct solar radiation for a water storage system that can be used in accordance with the climate of Malaysia country. In general, this research is related to thermal efficient water heating system, specifically to improve the water heating system that exists nowadays. The focus is to improve the thermal efficiency by adding different absorber bed designs. Based on experimental results shown the temperature of the water increases more efficient and faster by using the curve reflector bed.